The Practices of Teaching Orientation and Mobility Skills to Students with Visual Impairment in Selected Tanzanian Universities - Shemndolwa Mwitango; Kenneth Muzata; Magdalene Simalalo (Indonesian Educational Research Journal, 2025)
The increased need for independence among individuals with visual impairment poses a deliberate prerequisite to equipping them with orientation and mobility skills.  This study aimed to investigate the practices of teaching orientation and mobility skills among university students with visual impairment in Tanzania.  Understanding the practices used, new and better policies can be developed to improve the training of orientation and mobility for students with visual impairments. The study employed an intrinsic case study design to generate in-depth information on training orientation and mobility for students with visual impairments. Purposively, 25 participants were selected to participate in the study, including students with visual impairment, orientation and mobility specialists, and administrators. Inductive thematic analysis using NVIVO was employed to make sense of data generated from two selected universities using interviews, focus group discussions, observation,s and documentary reviews.  The findings revealed that orientation and mobility are taught in an unstructured environment without proper guidelines to guide the teaching process. Based on the findings, it is recommended that orientation and mobility training should be incorporated into the university policy and curriculum to allow students with visual impairment to learn orientation and mobility systematically for proper mastery of the skills.